Analisis Implementasi Integrated Reporting pada PT XL Axiata Tbk berdasarkan IR Framework - Diki Ibrahim; Nisrina Jaesa; Nurul Hasanah; Rahmawati; Holiawati (Paulus Journal of Accounting (PJA), 2024)
Analysis of Integrated Reporting Implementation at PT XL Axiata Tbk Based on the IR Framework. This research examines the implementation of Integrated Reporting (IR) at PT XL Axiata Tbk, referencing "The International <IR> Framework" published by the International Integrated Reporting Council (IIRC) in 2013. A comparative statistical analysis was used to assess the compliance level with the required IR elements. The findings indicate that PT XL Axiata Tbk has implemented the IR elements with a 93% compliance rate, demonstrating a strong commitment to transparency and integrated performance reporting. However, some elements have not been fully applied, necessitating more comprehensive information and explanations for the omission of certain elements. This study is limited to PT XL Axiata Tbk and the year 2022.